Understanding the difference in softness of Australian Soft Rolling Skin wool and conventional Merino wool. Issue 17 (September 2022) - Yu, Hao; Hurren, Christopher; Liu, Xin; Wang, Xungai
Softness is one of the key elements of textile comfort and is one of the main considerations when consumers make purchasing decisions. In the wool industry, softness can reflect the quality and value of wool fibers. There is verifiable difference in subjective softness between Australian Soft Rolling Skin (SRS) wool and conventional Merino (CM) wool, yet the key factors responsible for this difference are not yet well understood. Fiber attributes, such as crimp (curvature), scale morphology, ortho-to-cortex (OtC) ratio and moisture regain, may have a significant influence on softness performance. This study has examined these key factors for both SRS and CM wool and systematically compared the difference in these factors. There was no significant difference in the crimp frequency between these two wools; however, the curvature of SRS wool was lower than that of CM wool within the same fiber diameter ranges (below 14.5 micron, 16.5–18.5 micron). This difference might be caused by the lower OtC ratio for SRS wool (approximately 0.60) than for CM wool (approximately 0.66). The crystallinity of the two wools was similar and not affected by the change in OtC ratio. SRS wool has higher moisture regain than CM wool by approximately 2.5%, which could reduce the stiffness of wool fibers. The surface morphology for SRS wool was also different from that of CM wool. The lower cuticle scale height for SRS wool resulted in its smoother surface than CM wool. This cuticle height difference was present even when they both had similar cuticle scale frequency.